2008
DOI: 10.1111/j.1743-6109.2008.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Worry, Desire, and Sexual Satisfaction and Their Association with Severity of ED and Age

Abstract: Introduction This study evaluates worry about sexual and relationship functioning, sexual desire, and sexual satisfaction as indicators of sexual quality of life in men of different age groups suffering from mild to severe erectile dysfunction (ED). Aim To increase insight in the mechanisms of some key indicators of sexual quality of life in different age groups. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These findings are consistent with widely held clinical impressions and published research concerning the overall responsiveness or refractoriness of different types of ED cases to tadalafil and other PDE5 inhibitors [28–31]. A recent European study demonstrated that men with less severe ED reported significantly higher sexual satisfaction than their counterparts with more severe dysfunction [32]. However, in contrast to our findings, these investigators also found that older men reported greater sexual satisfaction than their younger counterparts (at each level of ED severity).…”
supporting
confidence: 92%
“…These findings are consistent with widely held clinical impressions and published research concerning the overall responsiveness or refractoriness of different types of ED cases to tadalafil and other PDE5 inhibitors [28–31]. A recent European study demonstrated that men with less severe ED reported significantly higher sexual satisfaction than their counterparts with more severe dysfunction [32]. However, in contrast to our findings, these investigators also found that older men reported greater sexual satisfaction than their younger counterparts (at each level of ED severity).…”
supporting
confidence: 92%
“…27 When ED has been present for a long time, and a couple has undergone an extended period without intimacy and/or sexual activity, it is often more difficult for them to benefit from efficacious treatment. 28 In general, the expectations of partners, which are possibly related to intimacy and emotional closeness, are likely to be substantially different from those of the patients, who measure success on the basis of the improved quality of their erections.…”
Section: Discussionmentioning
confidence: 99%
“…ED may have a direct association with poorer MH, but it may also be hypothesized that the association between ED and MH is influenced through mediating factors, such as satisfaction with and importance attached to sex life. On the one hand, studies found that ED was associated with dissatisfaction with and importance attached to sex life [12–16], and on the other hand, it is likely that satisfaction with and importance attached to sex life are associated with poor MH [17].…”
Section: Introductionmentioning
confidence: 99%